The Challenges Faced By Educators in Online Teaching during the Covid-19 Pandemic Outbreak - Sabir Ahmad, Sarah; Mat Seman, Mhd Azmin; Zakaria, Azfahanee (English Education Department, Faculty of Teacher Training and Education, Universitas PGRI Adi Buana Surabaya, 2021)
Since the pandemic attack the whole world, various research has been conducted related to the challenges of online learning. Focus has always been on the issues faced by the students, but lack of research has been to done from the educators’ perspective. Therefore, this research aims to identify the issues and challenges faced by the educators in online teaching. The issues that the researchers identified are technology, lack of training and lack of tools and materials make it difficult for the educators to adapt with the changes from teaching in the physical classroom to a virtual classroom which exposes the educators to a new teaching environment and this imposed countless challenges. The research method that is used in this research is simple random sampling where the sample size of this study is around 30 educators which focus on the educators that engage in online teaching at the age range between 21 years old until 60 years old. The data was collected through a questionnaire and the questionnaire is divided into three different sections. The data analysis procedure used in this research is frequency analysis to offer the researcher to analyze the data of the questionnaire. It was identified majority of the respondents are facing challenges with online teaching which decrease their motivation and productivity and contribute to low satisfaction and outcomes in their delivery of lectures.